Personality Traits - Fung, L.; Durand, Robert (John Wiley and Sons, inc, 2014)
Personality captures a person’s essence. Understanding one’s personality helps explain and predict the decisions an individual makes and what a person will do. This chapter focuses on the predominant structural model of personality — the Five-Factor Model — which encapsulates personality using five higher-order traits: Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to Experience/Intellect. The Five-Factor Model is rooted in biology and is genetically based. Personality traits are a major aspect of risk taking and overconfidence behaviors. Understanding personality can improve decision-making if it helps to regulate and override dispositional tendencies leading to suboptimal outcomes.